Stand growth scenarios for Tectona grandis plantations in Costa Rica - Pérez, D.; Kanninen, M. (2005)
Management scenarios with rotation lengths of 20 and 30 years were developed for different site qualities (high, medium and low) under two different management options (high individual tree growth versus high stand growth) for teak (Tectona grandis L.f.) in Costa Rica. The scenarios are based on data collected in different regions in Costa Rica, representing different site conditions, offering a variety of possible management options for high-quality teak yield. Three competition indices were used for modeling the competition and for the definition of intensities and the plantation age at thinning. The maximum site occupation (MSO) and the Reineke density index (RDI) provide conservative stand density management limits, resulting in the need to execute several thinning frequently. The competition factor (CF) matches the field observations and seems to be more appropriate for the growth characteristics of the species. Final stand densities varied between 120 and 447 trees ha-1, with mean diameter at breast height (dbh) of 24.9–47.8 cm, and mean total heights between 23.0 and 32.4 m, depending on rotation length and site quality. The mean annual increment of total volume (MAIVol) at the end of the rotation varied from 11.3 to 24.9 m3 ha-1 year-1, accumulating a total volume over rotation of 268–524 m3 ha-1. The most suitable scenario for teak plantations for high-quality sites is the 30-year-rotation scenario with five thinnings of intensities between 20 and 50% (of the standing trees) at the ages of 4, 8, 12, 18 and 24 years. After the sectioning of the merchantable stem in 4-m length logs, the merchantable volume varied between 145 and 386 m3 ha-1, with an estimated heartwood volume of 45–195 m3 ha-1, both depending on rotation length and site quality.